Russia–EU energy dialogue in 2000–2014: Key priorities, stages, contradictions, and outcomes - O. N. Yudina (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Energy cooperation was one of the cornerstones of the European Union–Rus- sia relations and, in turn, was, to a large extent, shaped by the progress of the EU-Russia Energy Dialogue, which developed from 2000 to 2014. On the basis of a consistent critical analysis of official sources, the paper identifies internal and external determinants of the Russia-EU Energy Dialogue and assesses its general logic and dynamics, as well as its key outcomes. The author concludes that in the first five years of the Energy Dialogue it was the European Union who acted as its driving force, as the EU sought not only to ensure the supplies of Russian energy resources, but also to take control over their production and transporta- tion. A careful comparison of the Russia-EU Energy Dialogue key dimensions and the provisions of the Energy Charter Treaty allowed the author to identify yet another aim of the European Union, namely, to impose on Moscow the prin- ciples of a common European energy policy. However, these efforts encountered strong opposition from the Russian government. From 2006–2007 the conflict of interests had become all the more evident, as considerable changes took place both in the internal energy policy of Moscow and Brussels and Russia’s inter- national position. As a result, the content and structure of the Energy Dialogue changed: discussions on the creation of a single energy community and energy markets were overshadowed by issues of strategic planning and development of an early warning mechanism. Therefore, by 2014, when the EU abandoned the Energy Dialogue, its potential had been to a large extent exhausted. Nevertheless, the Dialogue provided Russia with extensive experience in interacting with the European Commission as a supranational body of the EU, and this experience might be in demand in the future.